Legal Aspects of Indemnification Clauses in Business Transactions in The Digital Age - Imam Al Hakim; Alip Rahman; Anom Sutrisno (Journal of Social Research, 2026)
The rapid development of digital technologies has transformed traditional business transactions into online platforms, introducing new challenges for legal certainty and consumer protection. In digital agreements, exoneration clauses often limit or eliminate the liability of business actors, raising concerns about fairness and legal enforceability. This study aims to examine the application and legal implications of exoneration clauses in digital business transactions in Indonesia, assessing their compliance with statutory provisions and their impact on consumers. The research employs a normative legal research approach, analyzing primary, secondary, and tertiary legal materials, including the Civil Code, Law Number 11 of 2008 concerning Electronic Information and Transactions, and Law Number 8 of 1999 concerning Consumer Protection. Data collection was conducted through library research, while descriptive qualitative analysis was used to synthesize legal norms, doctrines, and expert opinions. Validity and reliability were ensured through triangulation of sources and systematic interpretation. The findings indicate that while exoneration clauses are permissible under the principle of freedom of contract, they cannot be applied arbitrarily. Clauses that disproportionately shift responsibility onto consumers violate the principles of good faith, fairness, and statutory consumer protection. Digital agreements must therefore balance contractual freedom with the protection of weaker parties. The study concludes that legal certainty in digital transactions depends not only on electronic signature recognition, but also on compliance with applicable laws, transparency, and adequate oversight to safeguard consumer rights.